The civil service$1 (Bs (3z(Bfast food approach(3y (Bto development policy-making in Bangladesh: s critique and agenda for reform - Rahman, Mohammad Mizanur; Quadir, Fahimul (2018)
Since Bangladesh$1 (Bs independence in 1971, the international donor community has largely shaped the nature and direction of the country$1 (Bs development plans. In most cases, successive governments have introduced development policies and programmes within the broad framework of international development co-operation that has frequently overlooked the local context. A significant part of the reason why donors have been able to play a dominant role in setting the country$1 (Bs development agenda is the inability of the civil service to serve as a challenge to externally-driven models of development. As is explored in this article, civil servants have lacked the capacity and political will to assume proactively a vital role in the policy-making process. This has resulted in a (3z(Bfast food approach(3y (Bwhich has allowed donors to have considerable control over the country$1 (Bs development. In response, civil service reform needs urgent and high priority attention in line with successful reform initiatives in other countries. - Reproduced.s
Keywords: Policy making - Bangladesh